Aproveitamento de resíduos de caranguejo Uçá gerados pelas barracas da praia do futuro como fonte alternativa de adubo orgânico em cultura de feijão Caupi - Araújo, Francisco José Freire de (2007)
The current management of the Urban Solids Residuals (URS) in most Brazilian cities have been considered to be slightly inefficient for the demand of the population, due to the rapid growth of the population in the last few decades and also because of their consuming lifestyle. The massive production of solid, liquids and gas residuals is also directly linked with the technology employed to benefit products extracted from nature, which most cases are difficult to be reabsorbed by the ecosystems. In this way, the urban cleanliness assumes an important role among the needs of the Brazilian society; gaining sanitary, economic, social and aesthetic importance. Studies conducted regarding the positive outcomes and the recycling of rubbish have shown its potentialities and an excellent alternative to the final disposal of many urban residuals. The current study highlights the problems and concerns with the URS, and suggests an alternative for the reduction of crab’s organic residuals generated by the restaurants at Futuro’s Beach in Fortaleza. In addition, the present study also proposes to other commercial establishments that produce such residuals, opportunity to transform them in organic fertilizers. The research aims to verify the viability for a better use of crab’s residuals generated by the restaurants at Futuro’s Beach as an alternative organic compost, working as a nutritional resource for a culture of Caupi beans. The choice for this culture is primarily due to its relevance to the wide population and also for being able to offer a quick response, as it is a culture of short cycle. Further to the study of the composition of the rubbish generated by such establishments, the research also aimed to analyse its chemical composition, its income and to look for productivity items such as plant’s height, number and size of string beans, weight of string beans, number of seeds per string beans, and the weight of a hundred seeds. For the purpose of this study, twenty two treatments, with four repetitions, which varied between the proportions of crab compost and chemical fertilizers in both of them were used in order to verify the results. The percentage of recyclable organic contents of this rubbish studied is about 87, 34%. However, crab’s residuals contributed with 52%. The income of this material is around 24%. Some parameters analysed like nitrogen, phosphorus, potassium, calcium and magnesium stood out due to its percentage values, found in this organic product, vary between 3 and 4 times more than those found in a sample of bovine compost. The data related to the productivity revealed that the treatments which obtained the best results had in common the presence of crab’s flour. This shows that by adding this organic compost enhances productivity parameters, which has a direct impact in the reduction of the amounts of chemical fertilizers used in the soil, a financial saving for the farmer and an adequate means for the organic solid residuals generated.